2009
DOI: 10.1111/j.1439-0531.2009.01406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Oxygen Tension on Cumulus Cell Viability of Canine COCs Matured in High‐Glucose Medium

Abstract: High in vitro oxygen (O(2)) tensions are associated with enhanced levels of reactive oxygen species and cumulus oocyte complex (COC) apoptosis. The objective of this study was to determine the influence of O(2) tension on cumulus cell (CC) viability from canine oocytes. Cumulus oocyte complexes were distributed into three groups (CG, T20 and T5) and two O(2) tension levels (20% and 5%). The control group (CG) was matured in vitro in a humidified atmosphere with 5% CO(2) in air in TCM199 with 26.19 mM sodium bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…5 vs 20%) (Rodrigues & Rodrigues 2010). Despite the presence of anti-apoptotic intracellular mechanisms acting via GSH against ROS (Silva et al 2009), having high lipid content in canine COCs can reduce GSH level and predispose them to oxidative damage and induce apoptosis in the cumulus cells (Silva et al 2009). This can contribute to lowered oocyte maturation rates (Kim et al 2007, Rodrigues & Rodrigues 2010.…”
Section: Oxygen Level and Ivmmentioning
confidence: 99%
See 2 more Smart Citations
“…5 vs 20%) (Rodrigues & Rodrigues 2010). Despite the presence of anti-apoptotic intracellular mechanisms acting via GSH against ROS (Silva et al 2009), having high lipid content in canine COCs can reduce GSH level and predispose them to oxidative damage and induce apoptosis in the cumulus cells (Silva et al 2009). This can contribute to lowered oocyte maturation rates (Kim et al 2007, Rodrigues & Rodrigues 2010.…”
Section: Oxygen Level and Ivmmentioning
confidence: 99%
“…Cumulus expansion (mucification) was described by the partial or complete loosening of cumulus cells into extracellular matrix surrounding the oocyte (Lee et al 2007a, Marei et al 2009, Silva et al 2009). COCs were assessed for expansion of cumulus cells at 24 h after the beginning of the culture and by the end of 52 h under a stereomicroscope.…”
Section: Assessment Of Cumulus Cell Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that there are several studies with O 2 in various species of mammals, revealing that the concentration of O 2 inside the uterus and oviducts usually fluctuates in the range of 2-8% [23], we used 5% of O 2 . Silva et al [15], showed in canine CCs that low O 2 tension was efficient in reducing apoptosis, working with 5% O 2 tension level and 5% CO 2 with a media supplemented with FCS, FSH, E 2 and HCG and high levels of glucose (5.5 mM), obtaining 38.9% of apoptosis. We obtained degenerated oocyte values of 65.5±7.3, 39.6±7.1 and 28.19±6.4 for media 1, 2 and 3 respectively with 5% CO 2 during maturation, and 71.42±12.23, 27.71±10.0 and 25.33±10.2 in case of culture with the presence of O 2 and N 2 .…”
Section: Results and Discusionmentioning
confidence: 99%
“…5% CO 2 is the most common concentration in IVM oocytes studies. In relation with oxygen, high in vitro O 2 tensions are associated with enhanced levels of reactive oxygen species and cumulus oocyte complex (COC) apoptosis, so low O 2 tension was efficient in reducing apoptosis in canine oocytes [15]. However there are no studies about the influence of nitrogen on canine oocyte maturation.…”
Section: Introductionmentioning
confidence: 99%